Unsteady Productivity Prediction for Three-Dimensional Horizontal Well in Anisotropic Reservoir. (6th December 2022) - Bi, Gang; Cui, Ying; Wu, Jiemin; Ren, Zongxiao; Han, Fei; Wang, Xin; Li, Mengmeng
Abstract : The reservoir anisotropy, perforating skin, and the compressibility of rock and fluids are important factors affecting horizontal well productivity. In this research, the finite volume method is adopted to develop a three-dimensional unsteady productivity prediction model for horizontal wells. An improved Peaceman well model is used to predict the productivity of horizontal wells. The influence of parameters, including the plane anisotropy, horizontal well length, and perforation skin on productivity were studied and the production law for horizontal wells was further analyzed. The accuracy of the model is verified by CMG reservoir simulation software. The following conclusions are obtained from study: first, the speed of pressure propagation in homogeneous and isotropic reservoir is faster than the anisotropic reservoir. Second, the flow rate of the horizontal well is U-shaped along the horizontal wellbore, and the contribution of perforation sections at both ends of horizontal wells to the total production is greater than that in the middle of horizontal wells. With the continuous production, the contribution of perforation sections at both ends gradually increases. Third, the accumulative production of a horizontal well increases with an increase in rock compressibility. The main reason is that with the increase of the elastic energy in reservoir, the accumulative production of the horizontal well under the same conditions gets higher. The proposed model can be used to predict pressure and production distribution for horizontal well in anisotropic reservoirs.